Relationship between in vitro cell culture cytotoxicity and sweat-extractable dithiocarbamates in natural rubber latex gloves - Elizabeth K Abraham; Kumari T V; Mohanan P V; Ramesh P; Remakumari V M; Roy Joseph (Journal of Rubber Research, 2005)
Cytotoxicity of some of the commercially available natural latex gloves was evaluated by in vitro cell culture test using L929 mouse fibroblast cell lines. The cytotoxic potential ranged from non-cytotoxic to severely cytotoxic for the different brands tsted. Since the cytotoxicity of latex products could be related to the release of leachable and toxic residual chemicals, the different brands of gloves were extracted in a physiologically simulated medium, namely, artificial sweat. The results revealed that a rubbe accelerator, zinc diethyldithiocarbamate (ZDEC), was present in the gloves as residues and released into the artificial sweat. The amount of ZDEC released into the artificial sweat (Sweat-extractable ZDEC) was estimated using high performance liquid chromatography. It was observed that there existed a linear relationship between the amount of sweat-extractable ZDEC and the cytotoxic potential of gloves represented in grades ranging from 0 to 3 as per ISO 10993-5 (1999) standard. This preliminary investigation showed that the amount of sweat-extractable ZDEC is a good indicator of the cytotoxicity potential of gloves and hence, the artificial sweat ectraction may be further developed as a reliable test method to screen new latex medical products/formulations.
Keywords: Artificial sweat; Cell culture; Cytotoxicity; HPLC; In vitro; Latex; Natural rubber; Surgical gloves; Sweat-extractable ZDEC